Physical and mechanical properties of bitumen modified with energy-saving additives based on surface-active substances - Sidun, Iurii; Chuguyenko, Sergiy; Koryuk, Volodymyr; Baranovych, Yaromyr; Teshchyshyn, Nazarii (Academic journal Industrial Machine Building Civil Engineering, 2025)
The article examines the influence of modern energy-saving additives based on surface-active agents available on the Ukrainian market on the physico-mechanical and performance properties of BND 70/100 paving-grade road bitumen. The relevance of the study is обусловлена the need to reduce the production and laying temperatures of asphalt concrete mixtures, which allows for lower energy consumption, reduced harmful emissions into the atmosphere, and improved technological efficiency of road construction without deterioration of pavement quality. The study analyzes the effect of various contents of energy-saving additives on the main quality indicators of bitumen. The relationships between changes in bitumen properties and additive concentration are presented, enabling the determination of optimal dosages from the perspective of ensuring the required performance characteristics of the bituminous binder. Special attention is paid to the investigation of adhesion properties of bitumen, in particular its adhesion to the surface of mineral aggregates and to glass, which serve as indicators of binder–aggregate interaction. The obtained results demonstrate a significant effect of surface-active additives on improving adhesion and enhancing bitumen resistance to stripping. Based on a comparative analysis of experimental data, it was established that, considering the overall set of investigated properties, the EN3 additive is the most effective energy-saving additive. Its application provides an optimal combination of improved bitumen properties and enhanced adhesion characteristics, confirming the feasibility of its use in warm mix asphalt production technologies.